Application of an Alternating Current Motor System Based on Fuzzy Adaptive Tracking Control for Nonlinear Systems - Liu, Chengwei; Wen, Na; Ma, Liming; Zhang, Xiaoyang; Gao, Jian (Informatica, 2024)
With the development of power electronics technology, microelectronics technology, and modern motor control theory, the fully digitalized permanent magnet synchronous motor servo system with high-performance control strategy has been rapidly promoted. The standard linear control approach is unable to satisfy the control needs of the high-performance system because the AC motor is a highly coupled nonlinear multivariable system. In light of this, the study suggests a novel fuzzy adaptive tracking control for nonlinear systems that is applied to the AC motor system. This control method is based on fuzzy logic systems and back stepping. The results indicated that for the same system equation, the control algorithm proposed by the study has a more accurate tracking effect compared to the comparison algorithm, and the control input u of the comparison algorithm has a much higher pulse than that of the study control input at the time when the system is just started. And every signal in the closed-loop system has strong tracking effect and is bounded. From the variation of rotor angular velocity x2, the initial oscillation was violent, but the system was gradually stabilized with the adjustment of parameters. The fuzzy adaptive back stepping control speed increased from decreasing to increasing before 0.55s and stabilized at 150 rads i.e. reference speed around 0.65s. The q-axis current was varied smoothly with the constant change of input voltage and the d-axis current was varied smoothly with the change of input voltage. The back stepping adaptive control method proposed by the research can accurately estimate the load torque, can accurately and quickly realize the speed in different motor tracking control advantages for the high performance control of nonlinear motors provide a better direction, and then can provide a new way for the improvement of the AC drive system, which is of great significance for research.